Observation of Continuing Currents Produced by Negative Cloud-to-Ground Flashes of Tropical Thunderstorm - Fauzi M.U.F.; Yusop N.; Ahmad M.R.; Baharudin Z.A.; Sabri M.H.M.; Takayanagi Y.; Salman A.R.; Morimoto T.; Ahmad B.H.; Baharuddin M.Z. (VDE Verlag GmbH, 2025)
This paper presents an observation of continuing current that was recorded from fast electric field and newly designed slow electric field antenna lightning measurement system for the first time in Malaysia. A total 41 negative cloud-to-ground (-CG) lightning flashes that has 107 continuing current from total of 8 thunderstorms occured on 17 November 2023 until 27 November 2023. On the other hand, 53 (49.5%) of the total continuing current that our system has recorded, are classified as long continuing current. There are 37 (34.6%) and 17 (15.9%) continuing current categorized as short and very short continuing current, respectively. Out of the observed lightning flashes, 33 displayed continuing current present in multiple return strokes continuously. Understanding the dynamics of these lightning flashes is crucial for improving safety measures and minimizing the associated risks during thunderstorm events. ? 2024 IEEE, ? VDE VERLAG GMBH Berlin Offenbach.